Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fsurg.2022.964203
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of Helicobacter pylori-related prognostic gene modification patterns in the tumour microenvironment of gastric cancer

Abstract: BackgroundHelicobacter pylori (HP) infection is one of the leading causes of gastric cancer (GC). However, the interaction between HP and the TME, and its carcinogenic mechanism remains unknown.MethodsThe HP-related prognostic genes were identified based on HP infection-related gene markers and HP infection sample datasets by risk method and NMF algorithm. Principal component analysis (PCA) algorithm was used to constructed the HPscore system. The “limma” R package was employed to determine differentially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…There may be common tumorigenic factors in gastric colliding tumors, such as gene mutation, H. pylori [7][8][9], Epstein-Barr virus infection, and radiation exposure, but there is no clear test [11]. A Japanese study showed that H. pylori infection was associated with an increased risk of gastric malignant lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…There may be common tumorigenic factors in gastric colliding tumors, such as gene mutation, H. pylori [7][8][9], Epstein-Barr virus infection, and radiation exposure, but there is no clear test [11]. A Japanese study showed that H. pylori infection was associated with an increased risk of gastric malignant lymphoma.…”
Section: Discussionmentioning
confidence: 99%